The Challenge of Using Technology to Innovation in the World of Education - Triyana I Gusti Ngurah (IAHN-TP Palangka Raya, 2022)
Technology is growing rapidly along with human needs to be able to simplify their lives, solve all problems more quickly, effectively, and efficiently. This development can be used to overcome the problems that are happening from 2020 until now, namely the COVID-19 pandemic. This paper discusses the challenges faced by the world of education in the use of technology, especially learning technology to support the implementation of quality learning during the covid 19 pandemic. The approach used is a library study approach which is collected through the search for journal articles related to technological challenges in educational innovation through google scholar. . Several journal articles that have been collected are then reviewed and analyzed to be able to find synergies of solutions offered in responding to technological challenges to provide innovation in digital era education. Disruptive innovation is an innovation that can simplify complicated and expensive conventional situations into products with better quality, attractiveness, and cheapness. Educational innovation is a transformation effort to get a better situation in the field of education or to improve aspects of education so that it is more effective and efficient. The principles of educational innovation contain several important things which include: innovation requires an analysis of various opportunities and possibilities that are open; innovation is conceptual and perceptual; innovation must start small; innovation is directed at leadership or pioneering. The general principle of using ICT in education is that it is effective and efficient, optimal, attractive, stimulates the creative thinking power of each student during the learning process.